Corrigendum to “Mg-doped CoCr₂O₄ nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage” [Chem. Eng. J. 535 (2026) 175200] - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Mg-doped CoCr2O4 nanoparticles with fast humidity sensing and mixed-controlled pseudocapacitive charge storage - K. Manjunatha; Shih-Lung Yu; Yi-En Wu; Ming-Kang Ho; Tsu-En Hsu; Yun-Tai Yu; B. Chethan; Mithun Prakash Ravikumar; Sakar Mohan; Tsung-Te Lin; Yi-Ru Hsu; Meng-Chu Chen; et al. (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Expansion of Molecular and Clinical Aspects of EPS8L2 (DFNB106)-Associated Hearing Loss Emphasizes a Potential Therapeutic Window - Daniel Owrang; Aboulfazl Rad; Masoome Alerasool; Susanne M. Kolb; Sheng-Jia Lin; Julia Doll; Neda Alidadiani; Shahrooz Ghaderi; Michaela A. H. Hofrichter; Reza Maroofian; Gaurav K. Varshney; Majid Mojarrad; et al. (Molecular Neurobiology, 2026)
EPS8L2, encoding EPS8 signaling adaptor L2 protein, is critical for stereocilia maintenance in cochlear hair cells. Four previously published families have replicated autosomal recessive non-syndromic hearing loss (DFNB106), yet the mutational and clinical spectrum remains poorly described. This study expands the mutational and clinical spectrum of EPS8L2 -associated hearing impairment by identifying five additional individuals in four families, more than doubling the number of reported cases to date, while going deeper into clinical aspects. These include two frameshift variants c.818_827dup, p.(Ala279Glyfs*36) and c.1430dup, p.(Val478Serfs*25), the first nonsense variant c.1878C > A, p.(Tyr626Ter), and the first missense variant with a spliceogenic effect c.767C > G, p.(Thr256Arg). Functional analysis confirmed that the c.767C > G variant causes exon 9 skipping, leading to a frameshift r.701_768del, p.(Gly234Alafs*55). A shared 4.17 Mb homozygous region among two unrelated Iranian families with this variant suggested a founder effect. These individuals uniquely showed U-shaped audiograms as a new association of more severe middle frequency hearing loss. Clinically, affected individuals presented moderate to moderately severe hearing loss that was mostly progressive, with an onset starting between the prelingual stage, extending postlingually. A younger sibling of the first European proband diagnosed with DFNB106 passed newborn hearing screening but was identified with compound heterozygous variants, underscoring the importance of early genetic testing. The progressive nature of EPS8L2 -related hearing loss is unusual for recessive non-syndromic forms and highlights the need for early monitoring and intervention. This work emphasizes the need for early molecular diagnosis and long-term clinical follow-up, while describing the natural history of EPS8L2 that will be important for future therapeutic development.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A novel adsorbent for efficient metal recovery from aqueous solutions: Carbon-coated oil-treated plastic granules as a sustainable approach to resource conservation - Farideh Pahlavan; Harpreet Kaur; Hamed Khodadaditirkolaei; Sk Faisal Kabir; Jung-Ying Lin; Laura K. G. Ackerman-Biegasiewicz; Elham H. Fini (Resources, Conservation and Recycling, 2025)

Influence of infant feeding practices on childhood dietary patterns in Upstate KIDS - Priscilla K. Clayton; Diane L. Putnick; Tzu-Chun Lin; Edwina H. Yeung (Appetite, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Fered-Fenton enhanced boron-doped diamond electrochemical oxidation for wastewater treatment: Antibiotic degradation, kinetics, and environmental effects - C. Chokejaroenrat; K. Poomipuen; K. Techauay; P. Weaoseng; U. Jermnak; H. Chokthaweepanich; N. Suriyachai; Y.-T. Lin; K. Imsilp; C. Sakulthaew (Journal of Water Process Engineering, 2025)

Cubic calcite and its structural phase transitions - Yang Yang; Yixin Lin; Xiangdong Ding; Christopher J. Howard; Ekhard K. H. Salje (Physics and Chemistry of Minerals, 2025)
Calcite, CaCO 3 , has been reported to exist in as many as seven different structural forms. The structure at room temperature and pressure (space group R $$\overline{3 }$$ 3 ¯ c , ‘Phase I’) was established by Bragg many years ago. A phase transition to a higher temperature phase (space group R $$\overline{3 }$$ 3 ¯ m, ‘Phase V’) was noted to occur at around 1240 K—this may proceed via an intermediate phase (space group again R $$\overline{3 }$$ 3 ¯ c , referred to as ‘Phase IV’). These phases differ primarily in the disposition of the CO 3 groups. Additional phases are found at higher pressures. We report a para-phase (parent phase, virtual prototype, aristotype) which assists in understanding the different phases, the phase transitions, and especially the domain structures and twin wall boundaries associated with these transitions. Molecular dynamics methods were used to study the temperature evolution of an isothermal-isobaric (NPT) ensemble of some 384,000 atoms. These computations reproduced the features of the known structures in R $$\overline{3 }$$ 3 ¯ c and R $$\overline{3 }$$ 3 ¯ m and then, at higher temperature, revealed a structure of the sodium chloride type (space group Fm $$\overline{3 }$$ 3 ¯ m ) in which the entities were the Ca 2+ cation and the CO 3 2− anion, this latter with effectively spherical symmetry. On this basis we have upon cooling a necessarily first order ferroelastic transition from cubic Fm $$\overline{3 }$$ 3 ¯ m to rhombohedral R $$\overline{3 }$$ 3 ¯ m , computed to occur at a simulated temperature of 1900 K, and a possibly continuous transition from the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c computed to occur at about 1525 K. The computations also allowed us to follow the domain structure and twin walls as a function of temperature, during both heating and cooling. The structure just below the R $$\overline{3 }$$ 3 ¯ m to R $$\overline{3 }$$ 3 ¯ c transition shows strong disorder in the orientation of the CO 3 groups, and this may be what is sometimes referred to as Phase IV. The domain structure just below the cubic to rhombohedral transition shows twinning of typical ferroelastic character. The doubling of the cell below the R $$\overline{3 }$$ 3 ¯ m to rhombohedral (on a doubled cell) R $$\overline{3 }$$ 3 ¯ c leads to a more complicated twin pattern. Indeed, the different structures can be identified from patterns of twinning. Differences between domain structures obtained on heating and cooling indicate extensive thermal metastabilities.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Epigenetic modifications control CYP1A1 Inducibility in human and rat keratinocytes - Lo-Wei Lin; Allison K. Ehrlich; Robert H. Rice (Toxicology and Applied Pharmacology, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

P21-52 Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - H. Hong; J. Li; T. Tong; X. Lin; Y. Xu; J. Lin; S. Liu; K. Luo; Z. Zhou (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Uranium-series and strontium isotope systematics in soil carbonates from dryland Critical Zones: Implications for soil inorganic carbon storage and transformation - Syprose K. Nyachoti; Victor H. Garcia; Curtis Monger; Craig Tweedie; Thomas E. Gill; Lixin Jin; Lin Ma (Geochimica et Cosmochimica Acta, 2024)

Potential application of Ginkgo biloba extract as a green corrosion inhibitor for carbon steel reinforcement in chloride-polluted simulated concrete pore solution - Ambrish Singh; K.R. Ansari; Siham K. AbdelRahim; Ismat H. Ali; Brahim EL Ibrahimi; Abdullah K. Alanazi; Muhammad Younas; Yuanhua Lin (Process Safety and Environmental Protection, 2024)

Future changes in intense tropical cyclone hazards in the Pearl River Delta region: an air-wave-ocean coupled model study - Zhenning Li; Jimmy C. H. Fung; Mau Fung Wong; Shangfei Lin; Fenying Cai; Wenfeng Lai; Alexis K. H. Lau (Natural Hazards, 2024)
The Pearl River Delta (PRD) region is highly vulnerable to tropical cyclone (TC)-caused coastal hazards due to its long and meandering shoreline and well-developed economy. With global warming expected to continue or worsen in the rest of the twenty-first century, this study examines the TC impact on the PRD coastal regions by reproducing three intense landfalling TCs, namely Vicente (2012), Hato (2017), Mangkhut (2018), using a sophisticated air-wave-ocean coupled model of high spatial resolution (1-km atmosphere and 500-m wave and ocean). The simulations are conducted using present-day reanalysis data and the same TCs occurring in a pseudo-global warming scenario projected for the 2090s. Results indicate that the coupled model accurately reproduces the air-wave-ocean status during the TC episodes. The 2090s thermodynamic status effectively increases the intensity of intense TCs, leading to more severe coastal hazards including gale, rainstorm, and storm surges and waves. On average, the maximum surface wind speed within 50–200 km to the right of the TC center can increase by 4.3 m/s (+22%). The 99th and the 99.9th percentile of accumulated rainfall will increase from 405 to 475 mm (+17.3%), and from 619 to 735 mm (+18.6%), respectively. The maximum significant wave height at the ocean is lifted by an average of 57 cm (+13.8%), and the coastline typically faces a 40–80 cm increase. The maximum storm surges are lifted by 30–80 cm over the open sea but aggravate much higher along the coastline, especially for narrowing estuaries. For Typhoon Vicente (2012), there is more than a 200 cm wave height increase observed both at open sea and along the coastline. In the 2090s context, a combination of mean sea level rise, storm surge, and wave height can reach more than 300 cm increase in total water level at certain hot-spot coastlines, without considering the superposition of spring tides.

Telomere dynamics during hibernation in a tropical primate - M. B. Blanco; D. L. Smith; L. K. Greene; A. D. Yoder; E. E. Ehmke; J. Lin; P. H. Klopfer (Journal of Comparative Physiology B, 2024)

Advancing ecological assessment of the Arabian Gulf through eDNA metabarcoding: opportunities, prospects, and challenges - Thadickal V. Joydas; Seerangan Manokaran; Jayanath Gopi; Jayachandran P. Rajakumar; Lin Yu-Jia; Moritz Heinle; Mazen K. Nazal; Karuppasamy P. Manikandan; Maryam Qashqari; Sowmya P. Mohandas; Syed A. Hussain; Rommel H. Maneja; et al. (Frontiers in Marine Science, 2024)
The Arabian Gulf (hereafter ‘the Gulf’) is renowned for its unique ecological characteristics and distinct marine life. It offers a diverse range of ecosystems that have adapted to the impacts posed by natural stress and human activities. Regular biomonitoring and diversity assessments are necessary to document the health of the Gulf ecosystem and to implement appropriate measures for effective conservation and management. Recently, environmental DNA (eDNA), a total pool of DNA isolated from environmental samples, has emerged as a highly effective tool for ecological studies. This review explores the opportunities, prospects, and challenges associated with employing eDNA metabarcoding in the ecological assessment and biomonitoring of the Gulf. It provides an overview of the status of the Gulf ecosystem and discusses the potential applications of eDNA metabarcoding in assessing biodiversity, monitoring invasive species, and evaluating ecosystem health. Additionally, the investigation addresses the challenges inherent in implementing this technique, considering environmental complexities, methodological intricacies, and data interpretation. Overall, this review emphasizes the immense potential of eDNA metabarcoding in advancing ecological assessment in the Gulf and calls for further research and collaboration to harness its benefits in this unique marine ecosystem.

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Aquaculture in Zambia: The Current Status, Challenges, Opportunities and Adaptable Lessons Learnt from China - Lin Zhang; Sahya Maulu; Fenglei Hua; Majory K. H. Chama; Pao Xu (Fishes, 2023)
As a land-locked country in Southern Africa, Zambia is rich in natural resources suitable for fish production. However, aquaculture is still in its infancy with enormous potential as most of Zambia’s fish now comes from capture fisheries. The aim of this study was to review the recent progress, status, challenges, and opportunities in Zambia’s aquaculture industry while drawing some lessons from China’s aquaculture experience, focusing on policy instruments, external support, quality seeds, and the investment environment for possible adaptation. To achieve this, we reviewed the existing literature about aquaculture in Zambia. This paper starts by reviewing the overall fishery sector’s developments based on the analysis of relevant statistics over decades before narrowing down to the aquaculture sub-sector. The review shows that aquaculture production has continued to expand significantly and will soon play a leading role in food and nutrition security in Zambia. However, the industry still faces major challenges relating to investments, science and technology, fish seed and feed, and an underdeveloped value chain besides the increasing demand for fish products. Nevertheless, great potential still exists to further develop the aquaculture sub-sector and meet the ever-growing demand for fish products caused mainly by the rapid population increase.

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Corrosion and bacterial growth mitigation in the desalination plant by imidazolium based ionic liquid: Experimental, surface and molecular docking analysis - Ambrish Singh; K.R. Ansari; Neeta Raj Sharma; Shivani Singh; Rahul Singh; Anu Bansal; Ismat H. Ali; Muhammad Younas; Abdullah K. Alanazi; Yuanhua Lin (Journal of Environmental Chemical Engineering, 2023)

Life-course exposure to ambient fine particulate matter and hypertension in adulthood: a longitudinal cohort study - Cui Guo; Ly-yun Chang; Yacong Bo; Changqing Lin; Alexis K. H. Lau; Tony Tam; Xiang Qian Lao (Environmental Science and Pollution Research, 2023)

Trametes suaveolens-derived biochar loaded on nanoscale zero-valent iron particles for the adsorption and reduction of Cr(VI) - W.-D. Wang; H.-T. Ma; W. Lin; P. Sun; L.-K. Zhang; J.-H. Han (International Journal of Environmental Science and Technology, 2022)

Determining tolerance levels for quality assurance of 3D printed bolus for modulated arc radiotherapy of the nose - T. Kairn; S. Talkhani; P. H. Charles; B. Chua; C. Y. Lin; A. G. Livingstone; S. K. Maxwell; T. Poroa; E. Simpson-Page; E. Spelleken; M. Vo; S. B. Crowe (Physical and Engineering Sciences in Medicine, 2021)

Coarser taxonomic resolutions are informative in revealing fish community abundance trends for the world’s warmest coral reefs - Yu-Jia Lin; Ruben H. Roa-Ureta; Abdullajid Usama Basali; Joselito Francis Albaran Alcaria; Reynaldo Lindo; Mohammad A. Qurban; Perdana K. Prihartato; Ali Qasem; Lotfi Rabaoui (Coral Reefs, 2021)

Antigen production and development of an indirect ELISA based on the nucleocapsid protein to detect human SARS-CoV-2 seroconversion - Marcelo S. Conzentino; Karl Forchhammer; Emanuel M. Souza; Fábio O. Pedrosa; Meri B. Nogueira; Sônia M. Raboni; Fabiane G. M. Rego; Dalila L. Zanette; Mateus N. Aoki; Jeanine M. Nardin; Bruna Fornazari; Hugo M. P. Morales; et al. (Brazilian Journal of Microbiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Diversity, Distribution, and Density of Marine Mammals Along the Saudi Waters of the Arabian Gulf: Update From a Multi-Method Approach - Lotfi Rabaoui; Ruben H. Roa-Ureta; Lamia Yacoubi; Yu-Jia Lin; Rommel Maneja; Thadickal V. Joydas; Premlal Panickan; Jinoy Gopalan; Ronald Loughland; Perdana K. Prihartato; Ali Qassem; Tyas I. Hikmawan; et al. (Frontiers in Marine Science, 2021)
Despite the important role of marine mammals in marine ecosystems and the imperative for their conservation, there is still a great lack of information on the diversity, distribution, and density of these animals in the Saudi waters of the Arabian Gulf. To fill this gap, an integrative data-collection approach including fishermen’s questionnaires, opportunistic sighting reports, and directed boat-based surveys, was undertaken between 2016 and 2020, leading to the first scientific report of marine mammal diversity, distribution, and density in the region. The results of the different approaches carried out during the study confirmed a high diversity of cetaceans on the west coast of the study area, with bottlenose dolphins ( Tursiops aduncus ), humpback dolphins ( Sousa plumbea ) and dugongs ( Dugong dugon ) as the most common species. While the two dolphin species were found to be widely distributed in both coastal and offshore waters, D. dugon appears to occur exclusively in coastal waters in the southern part of the study area, mainly in the Gulf of Salwah. The presence of both species of dolphins increased during the summer months and in the vicinity of the numerous oil and gas facilities in this region. The distribution of the observed dolphins was found mostly within a 10–20 km radius around each facility. Other cetacean species observed less frequently in the area include Bryde’s whale ( Balaenoptera edeni ), killer whale ( Orcinus orca ), common dolphin ( Delphinus delphis ) and finless porpoise ( Neophocaena phocaenoides ). Regarding the density of marine mammals in the region, boat-based surveys confirmed the results of fishermen’s questionnaires and reports of opportunistic sightings, with bottlenose and humpback dolphins being the most abundant species. These results provide a baseline for policies oriented to the conservation of mammals in the Saudi waters of the Arabian Gulf.

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

Strengths and weaknesses in the long‐term sustainability of two sympatric seabreams ( Argyrops spinifer and Rhabdosargus haffara , S paridae) - Yu‐Jia Lin; Lotfi Rabaoui; Rommel H. Maneja; Abdu Rahiman Kambrath Pulikkoden; Panickan Premlal; Zahid Nazeer; Mohammad A. Qurban; Khaled Abdulkader; Perdana K. Prihartato; Ali M. Qasem; Nabil Fita; Ruben H. Roa‐Ureta (Journal of Fish Biology, 2021)
Argyrops spinifer and Rhabdosargus haffara are two sympatric seabream species making important contributions to fisheries landings in the western Arabian/Persian Gulf. We identified the strengths and weaknesses in the long‐term sustainability of A. spinifer and R. haffara stocks by integrating multiple sources of data, including fisheries catch and effort statistics, life history traits, scientific trawl surveys and historical length frequency distribution. Four strengths were identified in A. spinifer : wide distribution of juveniles, positive association to the network of de facto fishing exclusion areas created by hundreds of oil‐gas facilities, early maturation and the existence of large and old individuals. A. spinifer suffers from two potential weaknesses: slow growth rate and higher exploitation pressure on the small‐sized individuals. R. haffara , on the other hand, has a strength of having a short life span and a fast growth rate, characteristics that make it robust to unfavourable conditions. R. haffara suffers from two weaknesses: the lack of association to the oil and gas facilities, and the preference for nearshore shallow waters with stronger negative anthropogenic impacts. Identified strengths and weaknesses of these two sparids provided a preliminary assessment about their long‐term sustainability, as well as a roadmap about how to develop different management strategies to meet specific objectives.

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Atrial fibrillation rhythm is associated with marked changes in metabolic and myofibrillar protein expression in left atrial appendage - Julie H. Rennison; Ling Li; Cheryl R. Lin; Beth S. Lovano; Laurie Castel; Sojin Youn Wass; Catherine C. Cantlay; Meghan McHale; A. Marc Gillinov; Reena Mehra; Belinda B. Willard; Jonathan D. Smith; et al. (Pflügers Archiv - European Journal of Physiology, 2021)

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization - Jinying Chen; Fan-Li Lin; Jacqueline Y. K. Leung; Leilei Tu; Jiang-Hui Wang; Yu-Fan Chuang; Fan Li; Hsin-Hui Shen; Gregory J. Dusting; Vickie H. Y. Wong; Leszek Lisowski; Alex W. Hewitt; et al. (Angiogenesis, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Advanced psychometric testing on a clinical screening tool to evaluate insomnia: sleep condition indicator in patients with advanced cancer - Chung-Ying Lin; Andy S. K. Cheng; Vida Imani; Mohsen Saffari; Maurice M. Ohayon; Amir H. Pakpour (Sleep and Biological Rhythms, 2020)
Purpose To examine the psychometric properties of the Sleep Condition Indicator (SCI) using different psychometric approaches [including classical test theory, Rasch models, and receiver operating characteristics (ROC) curve] among patients with advanced cancer. Methods Through convenience sampling, patients with cancer at stage III or IV ( n = 859; 511 males; mean ± SD age = 67.4 ± 7.5 years) were recruited from several oncology units of university hospitals in Iran. All the participants completed the SCI, Insomnia Severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), Hospital Anxiety and Depression Scale (HADS), General Health Questionnaire (GHQ), and Edmonton Symptom Assessment Scale (ESAS). In addition, 491 participants wore an actigraph device to capture objective sleep. Results Classical test theory [factor loadings from confirmatory factor analysis = 0.76–0.89; test–retest reliability = 0.80–0.93] and Rasch analysis [infit mean square (MnSq) = 0.63–1.31; outfit MnSq = 0.61–1.23] both support the construct validity of the SCI. The SCI had significant associations with ISI, PSQI, ESS, HADS, GHQ, and ESAS. In addition, the SCI has satisfactory area under ROC curve (0.92) when comparing a gold standard of insomnia diagnosis. Significant differences in the actigraphy measure were found between insomniacs and non-insomniacs based on the SCI score defined by ROC. Conclusion With the promising psychometric properties shown in the SCI, healthcare providers can use this simple assessment tool to target the patients with advanced cancer who are at risk of insomnia and subsequently provide personalized care efficiently.

A System Level Analysis of Coastal Ecosystem Responses to Hurricane Impacts - C. J. Patrick; L. Yeager; A. R. Armitage; F. Carvallo; V. M. Congdon; K. H. Dunton; M. Fisher; A. K. Hardison; J. D. Hogan; J. Hosen; X. Hu; B. Kiel Reese; et al. (Estuaries and Coasts, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Noise exposure assessment and prevention around high-speed rail - K.-T. Tsai; M.-D. Lin; Y.-H. Lin (International Journal of Environmental Science and Technology, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Unidirectional monosynaptic connections from auditory areas to the primary visual cortex in the marmoset monkey - Piotr Majka; Marcello G. P. Rosa; Shi Bai; Jonathan M. Chan; Bing-Xing Huo; Natalia Jermakow; Meng K. Lin; Yeonsook S. Takahashi; Ianina H. Wolkowicz; Katrina H. Worthy; Ramesh Rajan; David H. Reser; et al. (Brain Structure and Function, 2019)

Aeromonas shuberti as a cause of multi‐organ necrosis in internal organs of Nile tilapia, Oreochromis niloticus - C Liu; O Q Chang; D F Zhang; K B Li; F Wang; M H Lin; C B Shi; L Jiang; Q Wang; S M Bergmann (Journal of Fish Diseases, 2018)
A disease with white spots in internal organs of Nile tilapia occurred in Zhanjiang, southern China. Multiple, white nodules, 0.8–2.2 mm in diameter, were scattered throughout the liver, spleen and kidney of diseased fish. Signs of nodules reproduced after artificial infection with the isolated strain. Isolated bacteria were Gram‐negative, facultative anaerobic, motile, short rod‐shaped, with a length of 1.2–2.2 μm. Morphological and biochemical tests, as well as phylogenetic analysis, all strongly indicated that the isolate from tilapia is identical to Aeromonas schubertii ( A. schubertii) which temporary named LF 1708 strain. Antibiotic sensitivity assays showed the LF 1708 is sensitive to 24 of 27 tested antibiotics. Pathogenicity test revealed that the isolate at the dose of 3.75 × 10 6 CFU /g killed 100% of experimental tilapia within 2 days and the dose of 1 × 10 7 CFU /g killed 100% of experimental zebrafish within 1 day. Histopathology of diseased tilapia infected with A. schubertii showed numerous necrotic lesions widely distributed in spleen, liver and kidney, and infiltration with a large number of bacteria. To our knowledge, this was the first report that associated A. schubertii with mortality in tilapia.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

Evaluation of soil erosion risk for watershed management in Shenmu watershed, central Taiwan using USLE model parameters - B. S. Lin; K. Thomas; C. K. Chen; H. C. Ho (Paddy and Water Environment, 2016)

Diversity and degradation mechanism of an anaerobic bacterial community treating phenolic wastewater with sulfate as an electron acceptor - X. J. Guo; Z. Y. Lu; P. Wang; H. Li; Z. Z. Huang; K. F. Lin; Y. D. Liu (Environmental Science and Pollution Research, 2015)

Accumulation of arsenic in rice plant: a study of an arsenic-contaminated site in Taiwan - S.-C. Lin; T.-K. Chang; W.-D. Huang; H.-S. Lur; G.-S. Shyu (Paddy and Water Environment, 2015)

Numerical modeling of a strong dust event over the south China region in March 2010 - Kim-Chiu Chow; Lin Su; Jimmy C. H. Fung; Hui Ma; Alexis K. H. Lau (Meteorology and Atmospheric Physics, 2014)

Characterization of baseline sensitivity and resistance risk of Colletotrichum gloeosporioides complex isolates from strawberry and grape to two demethylation-inhibitor fungicides, prochloraz and tebuconazole - X. F. Xu; T. Lin; S. K. Yuan; D. J. Dai; H. J. Shi; C. Q. Zhang; H. D. Wang (Australasian Plant Pathology, 2014)

The association between chronic osteomyelitis and increased risk of diabetes mellitus: a population-based cohort study - S.-Y. Lin; C.-L. Lin; C.-H. Tseng; I.-K. Wang; S.-M. Wang; C.-C. Huang; Y.-J. Chang; C.-H. Kao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Erratum to: Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Molecular characterization of domestic and exotic potato virus S isolates and a global analysis of genomic sequences - Y.-H. Lin; J. A. Abad; C. J. Maroon-Lango; K. L. Perry; H. R. Pappu (Archives of Virology, 2014)

Development of a selective and differential medium for capsulated L actococcus garvieae - C‐I Chang; C‐F Lee; J‐M Tsai; C‐C Wu; L‐H Chen; S‐C Chen; K‐J Lin (Journal of Fish Diseases, 2014)
A selective and differential medium termed ‘ LG agar’ was developed for the isolation and presumptive identification of L actococcus garvieae that results in black colonies with red halos. In this study, all 14 strains of L . garvieae and only 9 of the 148 strains representing 38 other species were able to grow on the LG agar. The nine viable strains on LG agar plates (including E nterococcus faecalis , E nterococcus faecium , L actococcus lactis , V ibrio fluvialis , V ibrio furnissii , V ibrio mimicus and V ibrio salmonicida ) were further differentiated from L . garvieae by various colours or colony features. Colonies isolated from the mixing culture and the infected giant sea perch using LG agar plates were all positively identified as L . garvieae by conventional tests and 16 S r DNA sequencing. Furthermore, LG agar discriminated capsulated strains of L . garvieae , which were believed to be correlated with pathogens of fish and shellfish, from non‐capsulated ones by colony appearances. The specificity and differentiating ability of LG agar suggest that this medium displays considerable potential for primary isolation and presumptive identification of L . garvieae from pathological and environmental samples.

Clinical characteristics and outcomes of patients with pleural infections due to Stenotrophomonas maltophilia at a medical center in Taiwan, 2004–2012 - M.-R. Lee; H.-C. Wang; C.-Y. Yang; C.-K. Lin; H.-Y. Kuo; J.-C. Ko; W.-H. Sheng; L.-N. Lee; C.-J. Yu; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Temporal variability of forest communities: empirical estimates of population change in 4000 tree species - Ryan A. Chisholm; Richard Condit; K. Abd. Rahman; Patrick J. Baker; Sarayudh Bunyavejchewin; Yu‐Yun Chen; George Chuyong; H. S. Dattaraja; Stuart Davies; Corneille E. N. Ewango; C. V. S. Gunatilleke; I. A. U. Nimal Gunatilleke; et al. (Ecology Letters, 2014)
Long‐term surveys of entire communities of species are needed to measure fluctuations in natural populations and elucidate the mechanisms driving population dynamics and community assembly. We analysed changes in abundance of over 4000 tree species in 12 forests across the world over periods of 6–28 years. Abundance fluctuations in all forests are large and consistent with population dynamics models in which temporal environmental variance plays a central role. At some sites we identify clear environmental drivers, such as fire and drought, that could underlie these patterns, but at other sites there is a need for further research to identify drivers. In addition, cross‐site comparisons showed that abundance fluctuations were smaller at species‐rich sites, consistent with the idea that stable environmental conditions promote higher diversity. Much community ecology theory emphasises demographic variance and niche stabilisation; we encourage the development of theory in which temporal environmental variance plays a central role.

Pressure-assisted cyclic washing of heavy-metal-contaminated sediments - C. E. Lin; P. K. A. Hong; H. Y. Chiu; R. Y. Surampalli; C. T. Lin; C. M. Kao (International Journal of Environmental Science and Technology, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Exposure to household painting and floor treatments, and parental occupational paint exposure and risk of childhood brain tumors: results from an Australian case–control study - Kathryn R. Greenop; Susan Peters; Lin Fritschi; Deborah C. Glass; Lesley J. Ashton; Helen D. Bailey; Rodney J. Scott; John Daubenton; Nicholas H. de Klerk; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Exposure to pesticides and the risk of childhood brain tumors - Kathryn R. Greenop; Susan Peters; Helen D. Bailey; Lin Fritschi; John Attia; Rodney J. Scott; Deborah C. Glass; Nicholas H. de Klerk; Frank Alvaro; Bruce K. Armstrong; Elizabeth Milne (Cancer Causes & Control, 2013)

The use of procalcitonin in the diagnosis of bone and joint infection: a systemic review and meta-analysis - C.-J. Shen; M.-S. Wu; K.-H. Lin; W.-L. Lin; H.-C. Chen; J.-Y. Wu; M. C.-H. Lee; C.-C. Lee (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Outcome of metastatic breast cancer in selected women with or without deleterious BRCA mutations - S. Bayraktar; A. M. Gutierrez-Barrera; H. Lin; N. Elsayegh; T. Tasbas; J. K. Litton; N. K. Ibrahim; P. K. Morrow; M. Green; V. Valero; D. J. Booser; G. N. Hortobagyi; et al. (Clinical & Experimental Metastasis, 2013)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

Bacteremia caused by Brevundimonas species at a tertiary care hospital in Taiwan, 2000–2010 - M. R. Lee; Y. T. Huang; C. H. Liao; T. Y. Chuang; C. K. Lin; S. W. Lee; C. C. Lai; C. J. Yu; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Assessment of nitrogen contamination of groundwater in paddy and upland fields - Y. H. Kao; C.-W. Liu; C. S. Jang; S. W. Zanh; K. H. Lin (Paddy and Water Environment, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Diagnostic performance of an enzyme-linked immunospot assay for interferon-γ in skeletal tuberculosis - C.-C. Lai; C.-K. Tan; W.-L. Liu; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients - C.-C. Lai; C. K. Tan; S. H. Lin; W. L. Liu; C. H. Liao; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Mobilization and transport of coarse woody debris to the oceans triggered by an extreme tropical storm - A. J. West; C.-W. Lin; T.-C. Lin; R. G. Hilton; S.-H. Liu; C.-T. Chang; K.-C. Lin; A. Galy; R. B. Sparkes; N. Hovius (Limnology and Oceanography, 2011)
A significant consequence of Typhoon Morakot in August 2009 was the production of vast volumes of driftwood in Pacific Asia. We have quantified the flux of this coarse woody debris (CWD) to the oceans from typhoon‐triggered landslides in Taiwan, where Morakot made landfall, by combining remote sensing (using FORMOSAT‐2 imagery and aerial photography), analysis of forest biomass, and field observations. A total of 3.8–8.4 Tg CWD was transported to the oceans, carrying 1.8–4.0 Tg of organic carbon. In addition to the local effects on the marine and coastal environment from such a highly concentrated flux of carbon and nutrients, storm‐driven mobilization of CWD may represent a significant, if infrequent, transfer of terrestrial biomass to the oceans. If the frequency of relatively rare, extreme storms such as Morakot increases in a changing climate, this transport mechanism may play an important role in feedbacks between global climate, storm intensity, and carbon cycling.

Investigation of the association between all-trans-retinol dehydrogenase (RDH8) polymorphisms and high myopia in Chinese - Yan-shu Yu; Lin-ling Wang; Ye Shen; Maurice K. H. Yap; Shea-ping Yip; Wei Han (Journal of Zhejiang University-SCIENCE B, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Declining drug resistance of Mycobacterium tuberculosis isolates from elderly patients in Taiwan, 2000–2008 - W.-L. Liu; C.-C. Lai; C.-K. Tan; S.-H. Lin; Y.-T. Huang; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The chondroprotective effects of ferulic acid on hydrogen peroxide-stimulated chondrocytes: inhibition of hydrogen peroxide-induced pro-inflammatory cytokines and metalloproteinase gene expression at the mRNA level - M. P. Chen; S. H. Yang; C. H. Chou; K. C. Yang; C. C. Wu; Y. H. Cheng; Feng-Huei Lin (Inflammation Research, 2010)

Optimization of product line design for environmentally conscious technologies in notebook industry - K. H. Lin; L. H. Shih; S. C. Lee (International Journal of Environmental Science and Technology, 2010)

The second prolactin receptor in Nile tilapia (Oreochromis niloticus): molecular characterization, tissue distribution and gene expression - Yong Zhang; Zijie Long; Yangyuan Li; Shibai Yi; Yu Shi; Xilan Ma; Weiren Huang; Danqi Lu; Pei Zhu; Xiaochun Liu; Zining Meng; Xigui Huang; et al. (Fish Physiology and Biochemistry, 2010)

Antibacterial effect of electrolysed acid water on the nasal discharge from patients with chronic rhinosinusitis - R.-S. Jiang; S.-H. Wu; K.-L. Liang; J.-F. Lin; M.-C. Su; W.-K. Chen; F.-J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Clinical and genotypic characteristics of extensively drug-resistant and multidrug-resistant tuberculosis - C. C. Lai; C. K. Tan; S. H. Lin; C. H. Liao; Y. T. Huang; C. H. Chou; H. L. Hsu; C. Y. Wang; H. I. Lin; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Impact of pneumococcal vaccines on invasive pneumococcal disease in Taiwan - W.-H. Liao; S.-H. Lin; C.-C. Lai; C.-K. Tan; C.-H. Liao; Y.-T. Huang; C.-Y. Wang; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

In vitro activities of doripenem and other carbapenems against clinically important bacteria isolated in intensive care units: nationwide data from the SMART Programme - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Multiple factors have shaped the phylogeography of Chinese spiny loach Cobitis sinensis in Taiwan as inferred from mitochondrial DNA variation - T.‐Y. Chiang; H.‐D. Lin; K.‐T. Shao; K.‐C. Hsu (Journal of Fish Biology, 2010)
Mitochondrial DNA cytochrome b sequences (1140 bp) in 61 specimens of Chinese spiny loach Cobitis sinensis from 12 drainages in Taiwan were identified as two major clades, exhibiting a southern and a northern distribution, north of TzengWen and south of TzengWen (including TzengWen), respectively. The divergence time between these two phylogroups was estimated at 7·34–9·06 million years before present ( b.p. ), but these two phylogroups were formed c. 3·41–4·23 and 2·22–2·75 M b.p. , respectively. Moreover, geological events have been recalculated that Taiwan Island emerged above sea level at an estimate of c . 4–5 M b.p. , and quickly became its present shape at c. 2 M b.p. through mountain building. These results suggest that these two major clades of C. sinensis in Taiwan might originate from two different continental populations, since the island's initial isolation in the Pliocene. Within southern Taiwan, the initial colonization was hypothesized to be in KaoPing River, followed by its northward dispersal. The high divergence between KaoPing and TzengWen was influenced by glaciations and landforms. Within north Taiwan, the colonization was from the Miaoli Plateau through western Taiwan to north‐eastern and northern Taiwan. This dispersal pattern is concordant with the previously proposed hypothesis. Apparently, both geological and phylogeographic evidence suggested that river capture of the upper Takia River by the LanYang River promoted range expansion in freshwater fishes and also indicated that the Central Range within Taiwan did not act as a barrier to the dispersal of C. sinensis .

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Molecular characterization of two potato virus S isolates from late-blight-resistant genotypes of potato (Solanum tuberosum) - Y. H. Lin; K. L. Druffel; J. Whitworth; M. J. Pavek; Hanu R. Pappu (Archives of Virology, 2009)

Nationwide surveillance of antimicrobial resistance among Haemophilus influenzae and Streptococcus pneumoniae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Nationwide surveillance of antimicrobial resistance among Enterobacteriaceae in intensive care units in Taiwan - S.-S. Jean; P.-R. Hsueh; W.-S. Lee; H.-T. Chang; M.-Y. Chou; I.-S. Chen; J.-H. Wang; C.-F. Lin; J.-M. Shyr; W.-C. Ko; J.-J. Wu; Y.-C. Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Relationships between physiological responses and presyncope symptoms during tilting up in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2008)

Treatment of polluted river water by a gravel contact oxidation system constructed under riverbed - D. F. Juang; W. P. Tsai; W. K. Liu; J. H. Lin (International Journal of Environmental Science and Technology, 2008)

Sensitivity of future ozone concentrations in the northeast USA to regional climate change - K. E. Kunkel; H.-C. Huang; X.-Z. Liang; J.-T. Lin; D. Wuebbles; Z. Tao; A. Williams; M. Caughey; J. Zhu; K. Hayhoe (Mitigation and Adaptation Strategies for Global Change, 2008)

Population structure and phylogeography of Aphyocypris kikuchii (Oshima) based on mitochondrial DNA variation - H.‐D. Lin; K.‐C. Hsu; K.‐T. Shao; Y.‐C. Chang; J.‐P. Wang; C.‐J. Lin; T.‐Y. Chiang (Journal of Fish Biology, 2008)
Aphyocypris kikuchii is a cyprinid species endemic to northern and eastern Taiwan and is the only primary freshwater fish native east of the Coastal Mountain Range. In total, 92 individuals of A. kikuchii from seven populations in three regions of the island were surveyed for mitochondrial DNA (mtDNA) variation. High haplotype diversity ( h = 0·989) and low nucleotide diversity ( π = 0·009) of mtDNA were detected. Negative values of Tajima’s D and unimodal mismatch distributions probably reflect a history of recent demographic expansions from small populations. Three major haplotype clusters displayed geographically non‐overlapping distributions, indicating a long‐term isolation between regions. Hierarchical analysis of molecular variance showed significant genetic structuring among populations ( Φ ST = 0·66). Significant haplotype heterogeneity was also detected among populations within regions ( Φ SC = 0·41, P Φ CT = 0·43, P c. 0·11–0·39 million years ago. Haplotypes of cluster B nested as interior nodes in the haplotype network, indicating that migrations from Shueilian (SL) populations to the northern region (cluster A) and to the eastern region (cluster C) may have occurred independently. Lineages A and B + C should be managed as two distinct evolutionarily significant units, while the northern, SL and southern groups should be managed as separate management units.

Ethmoid sinus mycology of chronic rhinosinusitis - R. S. Jiang; K. L. Liang; J. Y. Shiao; J. F. Lin; M. C. Su; C. H. Hsin; F. J. Lu (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Development of a biofeedback tilt-table for investigating orthostatic syncope in patients with spinal cord injury - David S. Liu; Walter H. Chang; Alice M. K. Wong; Shih-Ching Chen; Kang-Ping Lin; Chien-Hung Lai (Medical & Biological Engineering & Computing, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Endosperm-specific hypomethylation, and meiotic inheritance and variation of DNA methylation level and pattern in sorghum (Sorghum bicolor L.) inter-strain hybrids - M. S. Zhang; H. Y. Yan; N. Zhao; X. Y. Lin; J. S. Pang; K. Z. Xu; L. X. Liu; B. Liu (Theoretical and Applied Genetics, 2007)

Arsenic Distribution in a Tilapia (Oreochromis mossambicus) Water-Sediment Aquacultural Ecosystem in Blackfoot Disease Hyperendemic Areas - S. -W. Wang; K. -H. Lin; Y. -M. Hsueh; C. -W. Liu (Bulletin of Environmental Contamination and Toxicology, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Apoptosis-dependent and -independent mechanisms mediate the phagocytic recognition/clearance of the HL60-A1 transfectants with prolonged survival - C.-L. Chou; L.-L. Chiang; C.-T. Yu; H.-C. Chen; K.-Y. Lee; S.-M. Lin; C.-D. Huang; W.-T. Liu; P.-C. Chou; C.-H. Wang; H.-C. Lin; H.-P. Kuo; et al. (Inflammation Research, 2007)

A dual site study of the rainwater chemistry within the Western Pacific region - K. M. Wai; S. H. Wang; P. A. Tanner; N. H. Lin (Journal of Atmospheric Chemistry, 2007)

Mitochondrial DNA phylogeography of Glyptothorax fokiensis and Glyptothorax hainanensis in Asia - X.‐L. Chen; T.‐Y. Chiang; H.‐D. Lin; H.‐S. Zheng; K.‐T. Shao; Q. Zhang; K.‐C. Hsu (Journal of Fish Biology, 2007)
Whole mitochondrial DNA cytochrome b sequences in 62 fish from 13 locations in Southeast China identified two major clades corresponding to two allopatric taxa, Glyptothorax fokiensis fokiensis and Glyptothorax fokiensis hainanensis . Reciprocal monophyly and a molecular clock separation between these two taxa of 2·3 million years indicate these taxa should be elevated to species. Mismatch distributions and Fu’s F S statistic suggest that both G. fokiensis and G. hainanensis have experienced recent population expansions. Analysis of molecular variance indicates that most of the genetic variation resides among populations within both species, with Φ ST = 0·645 for G. fokiensis and 0·801 for G. hainanensis , suggesting restricted gene flow among populations. Significant correlations between the geographic and the genetic distances provide support for the importance of geographic isolations between populations. Nested clade analysis also confirms low levels of genetic exchanges between the two major groups and between populations within each group. The phylogeographical pattern among populations of Glyptothorax in East Asia can be attributed to historical fragmentations, demographic expansions and occasional long‐distance dispersals stimulated by tectonic activity and Ice Age climate changes.

Pressure effect on the electronic structure of iron in (Mg,Fe)(Si,Al)O3 perovskite: a combined synchrotron Mössbauer and X-ray emission spectroscopy study up to 100 GPa - J. Li; W. Sturhahn; J. M. Jackson; V. V. Struzhkin; J. F. Lin; J. Zhao; H. K. Mao; G. Shen (Physics and Chemistry of Minerals, 2006)

Tissue Accumulation of Arsenic Compounds in Aquacultural and Wild Mullet (Mugil cephalus) - C.-W. Liu; K.-H. Lin; C.-S. Jang (Bulletin of Environmental Contamination and Toxicology, 2006)

Organic Matter Stable Isotope (δ13C, δ15N) Response to Historical Eutrophication of Lake Taihu, China - Jinglu Wu; Lin Lin; Michael K. Gagan; Gerhard H. Schleser; Sumin Wang (Hydrobiologia, 2006)

Isolation and Characterization of Two Phenol-Degrading Yeast Strains from Marine Sediment - Z. Hu; Y. R. Wu; B. K. Lin; K. Maskaoui; D. H. Zhuang; T. L. Zheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Enhancement of chemosensitivity toward peplomycin by calpastatin-stabilized NF-κB p65 in esophageal carcinoma cells: possible involvement of Fas/Fas-L synergism - T.-L. Liu; H. Shimada; T. Ochiai; T. Shiratori; S.-E. Lin; M. Kitagawa; K. Harigaya; M. Maki; M. Oka; T. Abe; M. Takiguchi; T. Hiwasa (Apoptosis, 2006)

Seismo-Geochemical Variations in SW Taiwan: Multi-Parameter Automatic Gas Monitoring Results - T. F. Yang; C.-C. Fu; V. Walia; C.-H. Chen; L. L. Chyi; T.-K. Liu; S.-R. Song; M. Lee; C.-W. Lin; C.-C. Lin (Pure and Applied Geophysics, 2006)

Risk Assessment of Arsenic Exposure from Consumption of Cultured Milkfish, Chanos chanos (Forsskål), from the Arsenic-Contaminated Area in Southwestern Taiwan - M.-C. Lin; H.-Y. Lin; H.-H. Cheng; Y.-C. Chen; C.-M. Liao; K.-T. Shao (Bulletin of Environmental Contamination and Toxicology, 2005)

Etoposide (VP-16) sensitizes p53-deficient human non-small cell lung cancer cells to caspase-7-mediated apoptosis - C.-C. Chiu; C.-H. M. Y. Lin; K. Fang (Apoptosis, 2005)

Fisheries of two tropical lagoons in Ghana, West Africa - H. R. Dankwa; J. M. Shenker; J. Lin; P. K. Ofori‐Danson; Y. Ntiamoa‐Baidu (Fisheries Management and Ecology, 2004)
The fisheries of two coastal lagoons, Keta and Songor, were studied as part of Ghana Coastal Wetlands Management Project (GCWMP) aimed at sustainable exploitation of wetland resources. Fish samples were obtained with seine nets and cast net as well as from local fishermen. Water quality parameters (pH, dissolved oxygen, temperature and turbidity) were similar in the two lagoons, except for salinity, which was significantly different ( P Sarotherodon melanotheron Rüppell, and the redchin tilapia, Tilapia guineensis (Bleeker), being the most important commercial fishes in both lagoons. The number of individuals for each species in Songor Lagoon were far more abundant, with densities several orders of magnitude higher than in Keta Lagoon. However, both species were significantly larger ( P S. melanotheron and T. guineensis respectively. Over‐fishing, use of small‐size mesh nets, limited mixing of marine and fresh water were some of the factors limiting fish production in both lagoons.

Adaptive processing bandwidth adjustment for laser Doppler flowmetry - Y. Y. Chen; Y. H. Lin; I. C. Jan; R. S. Liu; N. K. Chou; G. -J. Jan (Medical & Biological Engineering & Computing, 2004)

Mapping of quantitative trait loci controlling low-temperature germinability in rice (Oryza sativa L.) - K. Fujino; H. Sekiguchi; T. Sato; H. Kiuchi; Y. Nonoue; Y. Takeuchi; T. Ando; S. Y. Lin; M. Yano (Theoretical and Applied Genetics, 2004)

Nonlinear Time Series Analysis of Volcanic Tremor Events Recorded at Sangay Volcano, Ecuador - K. I. Konstantinou; C. H. Lin (Pure and Applied Geophysics, 2004)

QSARs for Predicting the Toxicity of Mixtures Containing Polar Narcotic Chemicals - Z. Lin; K. Yin; C. Wu; L. Wang; H. Yu (Bulletin of Environmental Contamination and Toxicology, 2003)

Outbreaks of an iridovirus disease in maricultured large yellow croaker, Larimichthys crocea (Richardson), in China - X H Chen; K B Lin; X W Wang (Journal of Fish Diseases, 2003)

Polychlorinated Biphenyls in Taiwanese Primipara Human Milk and Associated Factors - H.-R. Chao; S.-L. Wang; L.-Y. Lin; H.-Y. Yu; Y.-K. Lu; W.-L. Chou; Y.-L. Guo; L. W. Chang (Bulletin of Environmental Contamination and Toxicology, 2003)

Establishment of cell lines from a tropical grouper, Epinephelus awoara (Temminck & Schlegel), and their susceptibility to grouper irido‐ and nodaviruses - Y‐S Lai; J A C John; C‐H Lin; I‐C Guo; S‐C Chen; K Fang; C‐H Lin; C‐Y Chang (Journal of Fish Diseases, 2003)
Four tropical marine fish cell lines have been established from the eye, fin, heart and swim bladder of grouper, Epinephelus awoara (Temminck & Schlegel). Optimum media and temperature conditions for maximum growth were standardized. The eye and swim bladder cells were mostly epithelial, but the fin and heart cells were mostly fibroblastic. The viability of cells was 95% after 1 year of storage in liquid nitrogen (−196 °C). Besides these four cell lines, previously established grouper brain, kidney and liver cell lines were also used for a viral susceptibility study which showed that all the cell lines were sensitive to grouper iridovirus, whereas only brain, fin and liver cell lines were susceptible to the yellow grouper nervous necrosis virus (a nodavirus). Electron microscopy studies of the grouper irido‐ and nodaviruses in ultrathin sections of infected cells showed an abundance of viral particles in the cytoplasm of the virus‐infected cells indicating the effective replication of these two viruses. It is suggested that these cell lines can be used for the isolation of putative fish specific viruses and provide a valuable tool to study the mechanisms of host–pathogen interactions. Furthermore, these cell lines upon transfection, using pEGFP‐C1 and pEGFP‐aMT 2.5 (ayu metallothionein promoter), produced significant fluorescent signals indicating their utility for exogenous studies.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Residential Water Supply as a Likely Cause of Community-Acquired Legionnaires' Disease in an Immunocompromised Host - Chen Y-S.; Lin W-R.; Liu Y-C.; Chang C-L.; Gan V-L.; Huang W-K.; Huang T-S.; Wann S-R.; Lin H-H.; Lee S.; Huang C-K.; Chin C.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

A genetic linkage map of Nicotiana plumbaginifolia/ Nicotiana longiflora based on RFLP and RAPD markers - T. Y. Lin; Y. Y. Kao; S. Lin; R. F. Lin; C. M. Chen; C. H. Huang; C. K. Wang; Y. Z. Lin; C. C. Chen (Theoretical and Applied Genetics, 2001)

Propagation of yellow grouper nervous necrosis virus (YGNNV) in a new nodavirus‐susceptible cell line from yellow grouper, Epinephelus awoara (Temminck & Schlegel), brain tissue - Y‐S Lai; S Murali; H‐C Chiu; H‐Y Ju; Y‐S Lin; S‐C Chen; I‐C Guo; K Fang; C‐Y Chang (Journal of Fish Diseases, 2001)
A nodavirus was isolated from diseased yellow grouper, Epinephelus awoara , larvae cultured in southern Taiwan. The histopathology and RT–PCR results confirmed that it was a fish nodavirus; its coat protein gene sequence was similar to that of red spotted grouper nervous necrosis virus (RGNNV) and it is named yellow grouper nervous necrosis virus (YGNNV). A new nodavirus‐susceptible cell line, grouper brain (GB) was established and characterized from the brain tissue of yellow grouper. The GB cells multiplied well in Leibovitz’s L‐15 medium supplemented with 10% foetal bovine serum at temperatures between 24 and 32 °C, and have been subcultured more than 80 times, becoming a continuous cell line. The GB cell line consists of fibroblast‐like cells and some epithelioid cells. The cell line yielded titres of YGNNV up to 10 8.5 TCID 50 mL –1 . The GB cells effectively replicated the virus at 28 °C, which could be purified to homogeneity by caesium chloride gradient centrifugation. Electron microscopy studies showed that purified virus particles were 25–30 nm in diameter. The cytoplasm of infected cells was filled with aggregates of virus particles. These results indicate that the GB cell line is a significant tool for the study of fish nodaviruses.

Molecular epidemiology of enterovirus 71 in Taiwan - P.-Y. Chu; K.-H. Lin; K.-P. Hwang; L.-C. Chou; C.-F. Wang; S.-R. Shih; J.-R. Wang; Y. Shimada; H. Ishiko (Archives of Virology, 2001)

Blood and Urine Cadmium Levels in Relation to Demographic and Life Style in Middle Aged and Elderly Men - Y. C. Chen; Y. S. Pu; R. S. Lin; C. Y. Yang; M. K. Lai; S. H. Liu; F.-C. Sung (Bulletin of Environmental Contamination and Toxicology, 2001)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Development of a plant regeneration system based on friable embryogenic callus in the ornamental Alstroemeria - H. -S. Lin; C. van der Toorn; K. J. J. M. Raemakers; R. G. F. Visser; M.J. De Jeu; E. Jacobsen (Plant Cell Reports, 2000)

Agricultural Chemicals in the Alluvial Aquifer of a Typical County of the Arkansas Delta - H. S. Lin; H. D. Scott; K. F. Steele; H. I. Inyang (Environmental Monitoring and Assessment, 1999)

Soil Leaching Column Chromatographic Technique for Estimation of Leaching Behavior of Atrazine, Deethylatrazine, Deisopropylatrazine, and Hydroxyatrazine on Soil - F. Xu *, , X.-M. Liang; B. Lin; F. Su; H. Zhong; K.-W. Schramm; A. Kettrup (Bulletin of Environmental Contamination and Toxicology, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Analysis of QTL×environment interaction for yield components and plant height in rice - J.-Y. Zhuang; H.-X. Lin; J. Lu; H.-R. Qian; S. Hittalmani; N. Huang; K.-L. Zheng (Theoretical and Applied Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Human T-lymphotropic Virus Type II Infection inVietnamese Thalassemic Patients - M. T. Lin; B. T. Nguyen; T. V. Binh; T. V. Be; T. Y. Chiang; L. H. Tseng; Y. C. Yang; K. H. Lin; Y. -C. Chen (Archives of Virology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identifying different types of de-differentiated microspores from indica-japonica F1 hybrids with subspecies-differentiating RFLP probes in rice - J. -H. Xie; M. -W. Gao; J. Lu; J. -Y. Zhuang; H. -X. Lin; H. -R. Qian; K. -L. Zheng (Theoretical and Applied Genetics, 1997)

The skin, tongue, and brain as favorable organs for hog cholera diagnosis by immunofluorescence - I. C. Pan; T. S. Huang; C. H. Pan; Shenq-Yi Chern; Shu-Hwae Lee; Y. L. Lin; B. Y. Huang; C. C. Lin; N. J. Li; J. P. Lin; Y. H. Yang; S. Y. Chiu; et al. (Archives of Virology, 1993)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)